Higher self-assessed subjective social status is associated with worse perception of others’ emotions - Victoria K. Lee; Mel W. Khaw; Rachel E. Kranton; Scott A. Huettel (Scientific Reports)
Abstract The ability to accurately perceive others’ emotions is arguably critical for successful social interaction and may facilitate upward social mobility through personal and career advancement. Yet, prior research suggests that individuals of lower social status are better at perceiving others’ emotions. These competing viewpoints lead to the question of whether emotion perception ability—often referred to as empathic accuracy—shapes or is shaped by social status. In a preregistered experiment (n = 1197), we tested these alternate perspectives and found a robust negative relationship between individuals’ self-reported social status and behavioral measures of emotion perception. These effects were limited to emotions expressed by an individual actor and did not extend either to emotions expressed in a group or to similar judgments in a nonsocial control context. In addition, we found preliminary evidence that self-assessed increases in social status over the lifespan were also associated with worse emotion perception. These patterns support the perspective that social status shapes emotion perception abilities, but importantly, this relationship depends on one’s subjective sense of their status, both in comparison to others and in evaluations of one’s own lifespan trajectory.